Modelling of transitions between L- and H-mode in JET high plasma current plasmas and application to ITER scenarios including tungsten behaviour. (30th June 2017) - Koechl, F.; Loarte, A.; Parail, V.; Belo, P.; Brix, M.; Corrigan, G.; Harting, D.; Koskela, T.; Kukushkin, A.S.; Polevoi, A.R.; Romanelli, M.; Saibene, G.; et al.
Abstract: The dynamics for the transition from L-mode to a stationary high Q DT H-mode regime in ITER is expected to be qualitatively different to present experiments. Differences may be caused by a low fuelling efficiency of recycling neutrals, that influence the post transition plasma density evolution on the one hand. On the other hand, the effect of the plasma density evolution itself both on the alpha heating power and the edge power flow required to sustain the H-mode confinement itself needs to be considered. This paper presents results of modelling studies of the transition to stationary high Q DT H-mode regime in ITER with the JINTRAC suite of codes, which include optimisation of the plasma density evolution to ensure a robust achievement of high Q DT regimes in ITER on the one hand and the avoidance of tungsten accumulation in this transient phase on the other hand. As a first step, the JINTRAC integrated models have been validated in fully predictive simulations (excluding core momentum transport which is prescribed) against core, pedestal and divertor plasma measurements in JET C-wall experiments for the transition from L-mode to stationary H-mode in partially ITER relevant conditions (highest achievable current and power, H 98, y 1.0, low collisionality, comparable evolution in P net / P L-H, but different ρ *, T i / T e, Mach number and plasma composition compared to ITER expectations). The selection of transport models (core: NCLASS + Bohm/gyroBohm in L-mode/GLF23 in H-mode) was determined by a trade-off between model complexity and efficiency. Good agreement between code predictions and measured plasma parameters is obtained if anomalous heat and particle transport in the edge transport barrier are assumed to be reduced at different rates with increasing edge power flow normalised to the H-mode threshold; in particular the increase in edge plasma density is dominated by this edge transport reduction as the calculated neutral influx across the separatrix remains unchanged (or even slightly decreases) following the H-mode transition. JINTRAC modelling of H-mode transitions for the ITER 15 MA / 5.3 T high Q DT scenarios with the same modelling assumptions as those being derived from JET experiments has been carried out. The modelling finds that it is possible to access high Q DT conditions robustly for additional heating power levels of P AUX ⩾ 53 MW by optimising core and edge plasma fuelling in the transition from L-mode to high Q DT H-mode. An initial period of low plasma density, in which the plasma accesses the H-mode regime and the alpha heating power increases, needs to be considered after the start of the additional heating, which is then followed by a slow density ramp. Both the duration of the low density phase and the density ramp-rate depend on boundary and operational conditions and can be optimised to minimise the resistive flux consumption in this transition phase. The modelling also shows that fuelling schemes optimised for a robust access to high Q DT H-mode in ITER are also optimum for the prevention of the contamination of the core plasma by tungsten during this phase.